2016
DOI: 10.1016/j.ccell.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Akt Regulation of Hypoxic Tumor Reprogramming

Abstract: SUMMARY Hypoxia is a universal driver of aggressive tumor behavior, but the underlying mechanisms are not completely understood. Using a phosphoproteomics screen, we now show that active Akt accumulates in the mitochondria during hypoxia and phosphorylates pyruvate dehydrogenase kinase 1 (PDK1) on Thr346 to inactivate the pyruvate dehydrogenase complex. In turn, this pathway switches tumor metabolism towards glycolysis, antagonizes apoptosis and autophagy, dampens oxidative stress, and maintains tumor cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
154
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(164 citation statements)
references
References 45 publications
7
154
1
2
Order By: Relevance
“…Simulation of a cell with IGF-1 or heat shock stress, induced translocation of AKT to the mitochondria within only several minutes after the stimulation, and the mitochondrial AKT was in its phosphorylated and activated form [22]. Young, et al, a study which profiled the mitochondrial phosphoproteome of prostate adenocarcinoma PC3 cells exposed to severe hypoxia found that active AKT accumulates in the mitochondria under hypoxia [23]. When Mitochondrial ATP-sensitive potassium channel (mitoKATP), a common effector of protective stimuli in myocardial ischemia-reperfusion injury (MIRI), opens it plays a physiologic role in triggering cardiomyocytes' energy homeostasis during MIRI [15].…”
Section: Discussionmentioning
confidence: 99%
“…Simulation of a cell with IGF-1 or heat shock stress, induced translocation of AKT to the mitochondria within only several minutes after the stimulation, and the mitochondrial AKT was in its phosphorylated and activated form [22]. Young, et al, a study which profiled the mitochondrial phosphoproteome of prostate adenocarcinoma PC3 cells exposed to severe hypoxia found that active AKT accumulates in the mitochondria under hypoxia [23]. When Mitochondrial ATP-sensitive potassium channel (mitoKATP), a common effector of protective stimuli in myocardial ischemia-reperfusion injury (MIRI), opens it plays a physiologic role in triggering cardiomyocytes' energy homeostasis during MIRI [15].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia induced AKT accumulation in mitochondria, and phosphorylation of PDK1 has recently been demonstrated to be an additional control mechanism in hypoxic tumour cell metabolism (Chae et al . ). Exacerbated glycolysis leads to accumulation of lactate that must be dealt with to ensure continued cellular function, which led to an interest in understanding the role of monocarboxylate (MCT) lactate/H + membrane symporters in tumour cells (Fig.…”
Section: General Introductionmentioning
confidence: 97%
“…Akt signaling regulates cellular energy metabolism and apoptosis via mechanisms that converge on mitochondria (Stiles, 2009), via its association with HK2 and VDAC (Gottlob et al, 2001), or via the phosphorylation of key proteins, such as BAD (Datta et al, 1997). In addition, Akt acts inside mitochondria, where it can phosphorylate compartment-specific substrates, including the previously cited CypD (Ghosh et al, 2015) and PDK1 (Chae et al, 2016). The intra-mitochondrial Akt activity contributes to apoptosis resistance and tumor growth and might provide a novel adaptive mechanism for tumor resistance to PI3K-based therapy (Ghosh et al, 2015).…”
mentioning
confidence: 99%